Kunci Kemerosotan Perilaku Moral Generasi Emas di Masa Depan - Wahyudi, Dede; Ulfiyah, Siti Lulu; Aprily, Nuraly Masum (Universitas Negeri Surabaya, 2024)
One of the problems that is always faced in big cities is traffic problems. Therefore, the national transportation system must develop its potential and role in realizing security, safety, order and smooth traffic. Legal awareness is needed both from law enforcement officers and the public, especially in this case traffic drivers. The problem in this paper is the issue of Generation Z's traffic awareness in motorbikes. The research method uses descriptive quantitative, the population is students studying in Surabaya using random sampling techniques. Data collection uses a questionnaire via the Google Form application and data analysis uses descriptive statistics. The results of the research show that the awareness indicators of generation z motorists in traffic look very good.